2023
DOI: 10.1021/acsomega.3c03368
|View full text |Cite
|
Sign up to set email alerts
|

18 kDa Translocator Protein TSPO Is a Mediator of Astrocyte Reactivity

Abstract: An increase in astrocyte reactivity has been described in Alzheimer’s disease and seems to be related to the presence of a pro-inflammatory environment. Reactive astrocytes show an increase in the density of the 18 kDa translocator protein (TSPO), but TSPO involvement in astrocyte functions remains poorly understood. The goal of this study was to better characterize the mechanisms leading to the increase in TSPO under inflammatory conditions and the associated consequences. For this purpose, the C6 astrocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Furthermore, reactive astrocytes in vivo show increased TSPO expression (Lavisse et al., 2012) in a variety of pathophysiological contexts (Nutma et al., 2021; Tournier et al., 2020; Victorio et al., 2023; Winkeler et al., 2012), and we have previously demonstrated that astrocyte reactivity correlates with altered metabolism in these cells in vitro (Robb et al., 2020). Moreover, recent in vitro work using C6 astrocytoma cells has demonstrated that overexpression of TSPO increases ROS production and mitochondrial density while reducing glucose consumption, without altering mitochondrial membrane potential (Tournier et al., 2023). This is suggestive of a shift in cellular metabolism not dissimilar to the data presented in our current study, and perhaps indicates a change to TSPO stoichiometry in conditions where it is overexpressed, potentially to alter the bioenergetic state of astrocytes or fuel metabolic responses to prolonged (24 h [present study] or overnight (Tournier et al., 2023)) proinflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, reactive astrocytes in vivo show increased TSPO expression (Lavisse et al., 2012) in a variety of pathophysiological contexts (Nutma et al., 2021; Tournier et al., 2020; Victorio et al., 2023; Winkeler et al., 2012), and we have previously demonstrated that astrocyte reactivity correlates with altered metabolism in these cells in vitro (Robb et al., 2020). Moreover, recent in vitro work using C6 astrocytoma cells has demonstrated that overexpression of TSPO increases ROS production and mitochondrial density while reducing glucose consumption, without altering mitochondrial membrane potential (Tournier et al., 2023). This is suggestive of a shift in cellular metabolism not dissimilar to the data presented in our current study, and perhaps indicates a change to TSPO stoichiometry in conditions where it is overexpressed, potentially to alter the bioenergetic state of astrocytes or fuel metabolic responses to prolonged (24 h [present study] or overnight (Tournier et al., 2023)) proinflammatory stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent in vitro work using C6 astrocytoma cells has demonstrated that overexpression of TSPO increases ROS production and mitochondrial density while reducing glucose consumption, without altering mitochondrial membrane potential (Tournier et al., 2023). This is suggestive of a shift in cellular metabolism not dissimilar to the data presented in our current study, and perhaps indicates a change to TSPO stoichiometry in conditions where it is overexpressed, potentially to alter the bioenergetic state of astrocytes or fuel metabolic responses to prolonged (24 h [present study] or overnight (Tournier et al., 2023)) proinflammatory stimulation. In support of this, recent evidence from a murine model of Zika virus infection (Victorio et al., 2023) suggests that TSPO expression may correlate with the extent of glial reactivity or pathological severity (i.e., potential contribution to cellular hypermetabolism) with increased glial TSPO being observed within a relatively short timeframe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation